Two quasi-experiments on cohesion metrics and program comprehension - Batista, Elienai B.; Sant’Anna, Cláudio; Silva, Bruno C. da (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2017: Anais do XI Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2017)
Cohesion represents the degree to which a software module is focused on a single responsibility. It believes that the more cohesive, the easier it will be to understand the source code of a module. However, there is no empirical evidence about the relationship between cohesion, quantified by metrics, and the effort for understanding programs. In this context, we conducted two quasi-experiments to evaluate the relationship between cohesion measurements and the effort spent to understand the source code of classes in object-oriented systems. The results provide no evidence that cohesion affects program comprehensibility.